Influence of P-Ca on cytokinins in xylem sap and on stomatal resistance in apple - Ramírez , Homero; Malendres-Álvarez, Aarón Isain; Zermeño-González, Alejandro; Jasso-Cantú, Diana; Villarreal-Quintanilla, José ´Ángel (Ecosistemas y Recursos Agropecuarios, 2021)
With the purpose to search upon the cytokinins origin, a study was conducted on the effects of prohexadione-ca (P-Ca) on cytokinins in xylem sap and on stomatal resistance in apple. Golden Delicious seedlings were sprayed with 100 ppm P-Ca. Stomatal leaf resistance was measured at intervals between 1 and 4 hours of spraying and 15 days after the treatment. Golden Delicious trees were sprayed with 200 ppm P-Ca two weeks after full bloom. At intervals between 1 and two weeks after P-Ca treatment, the main de-shooted stem was removed from root system and xylem sap was collected for cytokinins analysis using the suction technique. Prohexadioneca significantly increased stomatal resistance (range 2.74-4.35 s/cm−1) when compared to control (range 2.12-3.44 s/cm−1); however, P-Ca did not modify the level of cytokinins in xylem sap since range values were between 0.10 to 0.20 μg kinetin equivalents/20 ml xylem sap for both, cytokinin and control.
Keywords: Apple; xylem sap; prohexadione-ca; cytokinins; stomatal resistance.